Sustainable production of recycled concrete aggregates by lime treatment and mechanical abrasion for M40 grade concrete - Prasad D.; Pandey A.; Kumar B. (My University, 2025)
Apart from aiding the environment, exploitation of recycled concrete aggregate (RCA) as a potential substitute for natural aggregates (NA) contributes to a framework of sustainable development as well as helps in maintaining an ecological balance by avoiding fast depletion of natural resources of aggregates. Therefore, in this investigation, the effects of mechanical beneficiation and lime treatment of coarse RCA on various properties of concrete were studied. The demolished concrete was crushed by hammer in size range of 25–4.75 mm, followed by grinding for 3, 5 and 8 min. It was found that 5 min of grinding was more effective based on the degree of success in the optimum removal of adhered mortar. Further, RCA ground for 5 min (MRCA) was graded into two different nominal sizes of 20 mm and 10 mm as per IS 383. Subsequently, MRCA was immersed in a lime solution of concentration varying from 1 N to 2.5 N for 3 and 7 days. These aggregates were termed as ‘LMRCA’. MRCA and LMRCA were used for partial replacement of coarse NA in M40 grade concrete at the rate of 10% up to 40% by weight. Various tests like compressive and flexural strength test and water absorption tests were performed. It was found that up to 30% NA can be replaced by MRCA or LMRCA in recycled aggregate concrete. But, the concrete admixed with LMRCA showed better properties than the concrete admixed with MRCA. Moreover, these experimental results were verified by employing microstructural and mineralogical analysis. In concrete admixed with LMRCA, the normality of lime solution was more dominant than the duration of LMRCA immersion in a lime solution. Also, the improvement in strength and water absorption of concrete admixed with LMRCA was proportional to the normality of lime solution. © 2020 Elsevier Ltd